rac-N-(4-Ethoxyphenyl)-3-hydroxybutanamide - James E. Hines III; Zechariah Myles; Garrick Breaux; Frank R. Fronczek; Rao M. Uppu (IUCrData, 2023)
In the title compound, racemic bucetin [systematic name: N-(4-ethoxyphenyl)-3-hydroxybutanamide], C12H17NO3, the molecule is in an extended conformation as illustrated by the C—O—C—C torsion angle [170.14 (15)°] in the ethoxy group and the subsequent C—N—C—C [−177.24 (16)°], N—C—C—C [170.08 (15)°] and C—C—C—C [171.41 (15)°] torsion angles in the butanamide chain. In the crystal, the O—H group donates an intermolecular O—H...O hydrogen bond to the amide carbonyl oxygen atom and also accepts an intermolecular N—H...O hydrogen bond from an adjacent N—H group. The former forms 12-membered dimeric rings about inversion centers, and the latter form chains in the [001] direction. The overall hydrogen-bonded network is two-dimensional, with no propagation in the [100] direction.